The Role of Blood Lactate Levels as Outcome Predictor of Isolated Traumatic Brain Injury Patients - Laode RA, Djoko W; -, Andi AI; -, Mansyur A; -, Burhanuddin B (BALI MEDICAL JOURNAL; Volume 1, Number 1, January-April 2012, 2013)
Objectives: Traumatic brain injury (TBI) is accompanied by regional alterations of brain metabolism, reduction in metabolic rates and possible energy crisis. This metabolic disturbance reflected by increase and accumulation of the brain lactate levels. Objective of this study was to determine the correlation between abnormalities in lactate metabolism for predicting neurologic outcome after moderate or severe traumatic brain injury. Methods: An observational prospective study in 60 patients with isolated TBI. Blood sample taken from vein of the limbs after underwent initial resuscitation. Serial assessment of the blood lactate level was measured in 1 st , 2 nd and 7 th day with Lact2 Roche Cobas® C-System. Neurologic outcome assessed on 7 th days using Modified GCS. Results: On initial assessment, 38.3% of patients with normal lactate (? 2 mMol/L), 61.7% of patients was hyperlactatemia ( > 2 mMol/L). In this study, it was obtained that the lower of GCS level, the higher of blood lactate level, and vice versa ( p = 0.033). In both treatment, there was a significant lactate clearance 24-hour as 37.96% ± 32.76 (p = 0.001) and 13.49% ± 40.32 (p = 0.011), respectively. No significant changes between blood lactate level on the 2 nd and 7 th day, both operative (p = 0.938; p > 0.05) neither conservative (p = 0.280; p > 0.05) patient. While, there was no correlation between neurologic outcome with 24-hour lactate clearance (p = 0.349). The higher of the initial blood lactate level, the patient’s outcome was worsen (p = 0.029). Conclusion: There is a significant correlation between blood lactate level and severity TBI according to GCS level. The lower GCS level, the higher blood lactate level and vice versa. This study also demonstrates that 24-hour lactate clearance did not affect patient’s outcome, but more influence by initial blood lactate level. Therefore, initial blood lactate level can used as an outcome predictor in TBI patients.
Keywords: traumatic, brain injury, lactate level, outcome